2022
DOI: 10.1038/s41593-022-01183-6
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells induce interferon-responsive oligodendrocytes and microglia in white matter aging

Abstract: A hallmark of nervous system aging is a decline of white matter volume and function, but the underlying mechanisms leading to white matter pathology are unknown. In the present study, we found age-related alterations of oligodendrocyte cell state with a reduction in total oligodendrocyte density in aging murine white matter. Using single-cell RNA-sequencing, we identified interferon (IFN)-responsive oligodendrocytes, which localize in proximity to CD8+ T cells in aging white matter. Absence of functional lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 72 publications
7
61
0
Order By: Relevance
“…Degradation of myelin sheaths of the neuronal system is accompanied by inflammatory processes closely related to aging in the brain (Kaya et al, 2022;Safaiyan et al, 2016), which in turn is increasingly associated which COVID-19 (Mavrikaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of myelin sheaths of the neuronal system is accompanied by inflammatory processes closely related to aging in the brain (Kaya et al, 2022;Safaiyan et al, 2016), which in turn is increasingly associated which COVID-19 (Mavrikaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of axonal integrity in white matter in the aging brain and in various neurodegenerative diseases is increasingly considered to result from homeostatic dysfunctions in the axon-OL unit 6,7,14,21,[54][55][56][57] . Yet, how OLs interact with and support myelinated axons throughout life is still enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Within the CNS, it is well-established that activated microglia express MHC-II (McGeer et al, 1988; Vass and Lassmann, 1990), but prior studies of MHC-II expression in mouse oligodendrocytes and astrocytes have yielded conflicting results (Falcão et al, 2018; Rostami et al, 2020; Stüve et al, 2002; Vass and Lassmann, 1990). In the context of MS, single cell RNA-seq in mouse models (Falcão et al, 2018; Kaya et al, 2022) and human brain tissue (Jäkel et al, 2019) identified subsets of mature oligodendrocytes that express IFN-inducible genes, including MHC-I and MHC-II genes, although only MHC-I associated signals was observed in human neuropathology (Höftberger et al, 2004). Our results suggest that acute stimulation with IFN-γ elicits the transcriptional upregulation of MHC-II genes only in microglia ( Fig.…”
Section: Discussionmentioning
confidence: 99%